Medicinal Plants Used in Wound Treatment in Veterinary Folklore in Turkey: A Literature Review - Cavus Alan, Seda; Ozen, Rahsan (Kafkas Univ, Veteriner Fakultesi Dergisi, 2021)
Medicinal plants have been widely used as a source of medicine in treating human and animal diseases from past to present in Turkey, as in almost all cultures. In this review article, a comprehensive literature search was done, and the plants used to treat wounds in the folklore of veterinary medicine in Turkey were compiled. In total, it was determined that plants from 69 families were used. It was determined that the most commonly used plants belong to the families of Asteraceae (24), Rosaceae (16), Lamiaceae (13). It has been observed that the use of Vitis sp., Pinus sp., Quercus sp., and species such as Rhus coriaria, Allium cepa, Olea europaea, Allium sativum spread over vast geography throughout the country. At the end of our review, it can be said that some of the plants used in wound treatment are used in humans and animals in our country and in different countries, and other plants have the potential to create a source for new drugs to be developed in wound treatment.
Türkiye’de Veteriner Hekimliği Folklorunda Yara Tedavisinde Kullanılan Tıbbi Bitkiler: Bir Literatür Değerlendirmesi
Keywords: Medicinal plants; Traditional treatment; Turkey; Veterinary folklore; Wound